2021
DOI: 10.1002/cac2.12239
|View full text |Cite
|
Sign up to set email alerts
|

BAIAP2L1 enables cancer cell migration and facilitates phospho‐Cofilin asymmetry localization in the border cells

Abstract: Dear Editor,Cancer invasion and metastasis are among the most clinically relevant cancer hallmarks. Identification of molecular pathways that contribute to cancer cell motility a crucial step in cancer invasion/metastasis is essential to understanding how cancer motility is regulated and may provide therapeutic targets for treating metastatic cancer. Brain-specific angiogenesis inhibitor 1-associated protein 2-like protein 1 (BAIAP2L1) is a novel oncoprotein whose high-leveled expressions have been correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…A recent study by Pipatpanyanugoon et al reported that BAIAP2L1 might promote cancer cell migration by modulating the phosphorylation of cofilin, 31 which was consistent with our finding that BAIAP2L1 might facilitate cancer cell motility; moreover, it has been proven that AKT signaling could dominate cofilin during cancer progression. 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 The AKT–cofilin axis is involved in chemotherapy resistance. 35 Further studies should explore whether cofilin is crucial in the AKT signaling pathway in promoting breast cancer progression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A recent study by Pipatpanyanugoon et al reported that BAIAP2L1 might promote cancer cell migration by modulating the phosphorylation of cofilin, 31 which was consistent with our finding that BAIAP2L1 might facilitate cancer cell motility; moreover, it has been proven that AKT signaling could dominate cofilin during cancer progression. 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 The AKT–cofilin axis is involved in chemotherapy resistance. 35 Further studies should explore whether cofilin is crucial in the AKT signaling pathway in promoting breast cancer progression.…”
Section: Discussionsupporting
confidence: 92%
“…[26][27][28][29][30] Our results revealed that BAIAP2L1 expression was increased in docetaxel-resistant cells and that BAIAP2L1 expression in breast cancer patients with poor chemotherapy responses, progression. [22][23][24][25][26][27][28][29][30][31][32][33][34] The AKT-cofilin axis is involved in chemotherapy resistance. 35 Further studies should explore whether cofilin is crucial in the AKT signaling pathway in promoting breast cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…This dual modulation inhibited src-driven proliferation, migration, and disrupted actin dynamics, impeding overall tumor dissemination ( 39 , 40 , 41 ). Nonphosphorylated cofilin is an activated form of cofilin and plays a crucial role in promoting actin polymerization and directional cell motility ( 42 ). The peptides also diminished NF-κB activity in DU-145 cells and reduced EGF-induced NF-κB nuclear translocation in MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 99%